Self-standing, binder-free electrospun Co3O4/carbon nanofiber composites for non-aqueous Li-air batteries - Song, Myeong Jun; Kim, Il To; Kim, Young Bok; Shin, Moo Whan (Electrochimica acta, 2015)
•Co3O4/carbon nanofiber composites were synthesized successfully.•The composites were synthesized via electrospinning and post thermal treatment.•The composites retained their three-dimensional self-standing structure.•The composites are used directly as the cathode for Li-air batteries.•The improved electrochemical performances are attributed to adding of ZIF-9. In this study, self-standing, binder-free ZIF-9 derived Co3O4/carbon nanofiber composites were synthesized via electrospinning and post thermal treatment for use as the cathode in a non-aqueous Li-air battery. Due to possessing a three-dimensional cross-linked web structure, Co3O4/carbon nanofiber composites are used directly as the cathode for Li-air batteries without the use of any binders or conductive metal foam, thus alleviating undesirable chemical reactions. We confirm that metallic cobalt (Co) in ZIF-9 is successfully oxidized to cobalt oxide (Co3O4) following two thermal treatment steps by analysis of XRD and XPS. The initial discharge capacity of Co3O4/carbon nanofiber composites exceeds 760 mAh g−1, which is a much higher discharge capacity compared to pristine carbon nanofiber (72 mAh g−1). Additionally, Co3O4/carbon nanofiber composite based cells exhibit improved cycling properties and a lower charge overpotential at various current densities. The improved electrochemical properties of the Co3O4/carbon nanofiber composites are attributed to the catalytic activity and stable contact with the homogeneously distributed Co3O4 in the carbon nanofiber structure. This work demonstrates that the synthesized Co3O4/carbon nanofiber composites could possibly be applied for use as next generation electrode materials for energy storage and conversion devices, particularly Li-air batteries.